An assessment of the physicochemical properties and toxicity potential of carwash effluents from professional carwash outlets in Gauteng Province, South Africa - Tekere, Memory; Sibanda, Timothy; Maphangwa, Khumbudzo Walter (Environmental science and pollution research international, 2016)
The assessment of the quality of carwash effluents has received scant attention as a potential source of public and environmental health hazard in South Africa as demonstrated by the lack of literature in this subject. The physicochemical quality and potential ramifications of carwash effluents on receiving waterbodies were investigated in this study. Grab effluent samples were collected from six carwash outlets in Gauteng Province of South Africa and analysed for selected physicochemical qualities including biological oxygen demand (BOD), oil and grease, total petroleum hydrocarbons-gasoline range organics (TPH-GRO), pH, dissolved oxygen (DO), total solids (TS) and total dissolved solids (TDS), electrical conductivity (EC), nutrients (nitrates, nitrites and phosphates), anionic surfactants and heavy metals (zinc [Zn], copper [Cu], lead [Pb] and chromium [Cr]). Further, the toxicity potential of the effluent samples was assessed using organisms from four trophic levels ranging from Selenastrum capricornutum (primary producer), Daphnia magna (primary consumer), Poecilia reticulata (secondary-tertiary consumer) and Vibrio fischeri (decomposer). High pollutant levels were observed in all effluents with BOD ranging from 27 ± 2.1 to 650 ± 4.9 mg/l, TDS from 362 ± 8.5 to 686 ± 8.5 mg/l, GRO-TPH from 0.01 ± 0.0 to 7.6 ± 0.2 mg/l, DO from 0.0 to 0.1 mg/l, Zn from 0.79 ± 0.08 to 20 ± 2.12 mg/l, Cu from 0.77 ± 0.03 to 13 ± 0.71 mg/l and oil and grease from 12 ± 2.8 to 43 ± 2.1 mg/l. Ammonium concentrations ranged from 0.4 ± 0.1 to 75 ± 6.4 mg/l; turbidity from 109 ± 0.7 to 4000 ± 29.7 mg/l, anionic surfactants from 1.4 ± 0.1 to 5.8 ± 0.3 mg/l and TPH from <0.01 to 7.6 mg/l. Toxicity assessment assays resulted in 100 % mortality for fish and Daphnia after 96 and 24 h, respectively, and significant bioluminescence and growth reduction in V. fischeri and algae after 15 min and 72 h, respectively. Most of the measured physicochemical parameters were in concentrations above the Environmental Management Agency (EPA) stipulated guidelines. Additionally, the effluents demonstrated acute toxicity against all four test species.